2013
DOI: 10.1161/strokeaha.113.001467
|View full text |Cite
|
Sign up to set email alerts
|

Single Subcortical Infarction and Atherosclerotic Plaques in the Middle Cerebral Artery

Abstract: Background and Purpose-Single subcortical infarction (SSI) may be classified as proximal SSI (pSSI) or distal SSI (dSSI) according to its extension to the middle cerebral artery (MCA). We investigated the differences between pSSI and dSSI in terms of their clinical features, lesion size, and the frequency of MCA plaques detected by high-resolution MRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
56
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 21 publications
7
56
0
Order By: Relevance
“…Conversely, there were no differences in the indicators of atherosclerosis and the prevalence of MCA plaque between large and small SSIs. The prevalence of superiorly located plaque, which was reported to be more closely associated with SSI, 4 was not different, either. Our data are consistent with a previous report showing that the axial diameter of diffusion-weighted image-identified SSI was not significantly different between patients with or without relevant MCA disease 2 and support the hypothesis that the SSI size difference may be explained by variations in the branching pattern of perforators (Figure 2) rather than the pathogenic mechanism (large artery atherosclerosis versus small artery disease).…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Conversely, there were no differences in the indicators of atherosclerosis and the prevalence of MCA plaque between large and small SSIs. The prevalence of superiorly located plaque, which was reported to be more closely associated with SSI, 4 was not different, either. Our data are consistent with a previous report showing that the axial diameter of diffusion-weighted image-identified SSI was not significantly different between patients with or without relevant MCA disease 2 and support the hypothesis that the SSI size difference may be explained by variations in the branching pattern of perforators (Figure 2) rather than the pathogenic mechanism (large artery atherosclerosis versus small artery disease).…”
Section: Discussionmentioning
confidence: 72%
“…4 Briefly, patients admitted to the Asan Medical Center between July 2011 and August 2012 were prospectively enrolled if they (1) had a single infarct identified with the diffusion-weighted image in the lenticulostriate arterial territory (basal ganglia, corona radiata, and internal capsule); (2) did not have significant (>50% stenosis) and relevant MCA disease; (3) had no identified source of the embolism (eg, emboligenic cardiac disease or significant [≥50%] stenosis of the relevant artery); and (4) the MCA vessel and the infarcted area could be demonstrated by sagittal image of high-resolution MRI performed on the fifth day after the initial MRI. The study protocol was approved by the local institutional review board, and written informed consent was obtained from each patient.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Yoon et al 17 and Chung et al 18 found that patients with pSSI had a higher prevalence of branch atheromatous plaque in MCA than those with dSSI …”
Section: Discussionmentioning
confidence: 99%
“…49 Similar studies have shown VW-MR imaging evidence of atherosclerotic plaque in the supplying artery of 52% of patients with MCA territory lacunar infarcts and 42% of patients with pontine infarcts, but normal MRA findings. 50,51 A VW-MR imaging study 52 that assessed the prevalence of MCA plaque both ipsilateral and contralateral to lenticulostriate territory infarcts in patients who had normal MRA findings found a similar prevalence (46% and 45%, respectively) bilaterally. This latter study did not report whether there was a difference in contrast enhancement between the plaques ipsilateral versus contralateral to the infarction.…”
mentioning
confidence: 97%